2013
DOI: 10.1111/1750-3841.12254
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Patulin from Apple Juice Using Ca‐Alginate‐Activated Carbon Beads

Abstract: This study aimed to investigate the adsorption of patulin from apple juice by Ca-alginate-activated carbon (Ca-alginate-AC) beads. The capacity of patulin was determined by high-performance liquid chromatography. The results showed that Ca-alginate-AC beads have significant ability to reduce patulin from contaminated apple juice. Furthermore, the adsorption process did not affect the quality of apple juice. The effects of contact time, initial patulin concentration, adsorbent dose, and temperature were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…This implied that the adsorption of AFB 1 and FB 1 on cross-linked chitosan was homogeneous adsorption. Besides, the coefficient K L in Langmuir model indicated the binding stability (Yue et al, 2013). The small K L values ranged from 0.0102 to 0.778 were obtained in this study (Table 3), which implied that the binding between toxins and adsorbent was strong.…”
Section: Adsorption Isothermmentioning
confidence: 53%
See 1 more Smart Citation
“…This implied that the adsorption of AFB 1 and FB 1 on cross-linked chitosan was homogeneous adsorption. Besides, the coefficient K L in Langmuir model indicated the binding stability (Yue et al, 2013). The small K L values ranged from 0.0102 to 0.778 were obtained in this study (Table 3), which implied that the binding between toxins and adsorbent was strong.…”
Section: Adsorption Isothermmentioning
confidence: 53%
“…Among these approaches, the addition of non-nutrition adsorbents into food and feed is regarded as the most effective and economical procedure to reduce the bioaccessibility of mycotoxin in gastrointestinal tract. So far, a large variety of adsorbents have been investigated for their capability to sequester mycotoxin in vitro and in vivo, such as inorganic adsorbents and their modified complexes (Dakovi c, Toma sevi cCanovi c, Rottinghaus, Matija sevi c, & Sekuli c, 2007;Mine Kurtbay, Bekçi, Merdivan, & Yurdakoç, 2008;Yue et al, 2013), organic adsorbents (Avantaggiato, Greco, Damascelli, Solfrizzo, & Visconti, 2014;Meca, Meneghelli, Ritieni, Mañes, & Font, 2012;Mine Kurtbay et al, 2008), and macromolecular polymers (Ramos, Hernandez, PlaDelfina, & Merino, 1996;Solfrizzo, Visconti, Avantaggiato, Torres, & Chulze, 2001). However, most of these adsorbents only sequester single or two toxins while presenting poor adsorption capability for other toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic parameters such as the Gibbs free energy change (△G °, KJ/mol), enthalpy change (△H °, KJ/mol), and entropy change (△S °, J/[mol·K]) are crucial and must be taken into consideration. These thermodynamic parameters for patulin adsorption process onto WICF were obtained at three different temperatures (277, 298, and 310 K), which can be estimated using the following equations as shown by Yue et al (): ΔGΟ=nRT ΔGΟ=ΔHΟTΔSΟ where T (K) is temperature and R (8.314 J/[mol·K]) is the gas constant; n is the characteristic constant from Freundlich model.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported on the degradation and/or detoxification of PAT or the reduction of its production in fruits (Assatarakul et al, 2012; Funes et al, 2013; Yue et al, 2013). The utilization of antagonistic microorganisms as biocontrol agents (BCAs) is promising because such agents have no known toxicity toward human health or ecosystem (Castoria et al, 2011; Zhu et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%